Effect of sample rugged surface on energy consumption and quality of plant-based food materials in convective drying. Issue 10 (12th July 2021) - Joardder, Mohammad U. H.; Alsbua, Reham; Akram, Washim; Karim, M. A.
Abstract: Drying is a simultaneous heat and mass transfer process aiming to remove water in order to extend the shelf life of food. However, food drying is very energy-intensive and time-consuming process and results in quality deterioration throughout drying. Energy requirement and the degree of quality degradation strongly depends on drying conditions. Although many studies investigated the effect of sample shape and size on drying kinetics and quality changes, there is no reported investigation on the effect of rugged surface or surface waviness on energy consumption and quality of food. In this study, relationships between sample corrugation and energy requirements and food in quality during drying have been investigated. The pattern of deformation and changes in esthetic appearance have also been investigated in this study. It was found that the amount of energy required during drying of brinjal, carrot, and radish varied significantly with the variation of sample shape. The minimum energy was required for drying samples with rugged surfaces; whereas the plane slice samples consumed higher energy. Similarly, changes in product quality attributes such as shrinkage, deformation and color were also different for these two types of samples.